CHARACTERISTICS OF STATIONARY HAZARDOUS AS REGARDS ANTHRAX AREAS IN ALTAI TERRITORY IN THE MODERN PERIOD - G. Kh. Bazarova; N. V. Luk’yanenko; E. N. Rozhdestvensky; I. P. Saldan; V. V. Shevchenko (Проблемы особо опасных инфекций, 2017)
Objective of the study is to comprehensively evaluate and forecast the development of epidemic process in case of anthrax in Altai Territory. Materials and methods. The data on stationary hazardous as regards anthrax areas (SHA) were obtained while analyzing cadastres of SHA in Altai Territory, as well as the reference book “Cadastre of stationary hazardous as regards anthrax areas in the Russian Federation”. Statistical and report forms from the institutions of the Rospotrebnadzor and Federal Service for Veterinary and Phytosanitary Surveillance in Altai Territory, and from Altai Plague Control Station were used for retrospective analysis of anthrax morbidity rates in Altai Territory over the period of 1953–2015. Laboratory investigations of field and clinical samples were carried out in compliance with Methodological Regulations 4.2.2413-08. Results and conclusions. Anthrax remains topical issue for Altai Territory as there are 1262 stationary hazardous areas situated in here, as well as registered animal and human infections. The density of such areas in Altai Territory is 7.5 times higher than across Siberia. Factors for the SHA formation and their sustainability are soilclimatic aspects of the region. The majority of hazardous areas are found in steppe and forest-steppe zones, predominantly along the cattle-driving paths. In Altai Territory, between 1953 and 2015, out of 1262 registered areas, 314 ones manifested epidemiological activity, including 246 new ones. Human infections were reported in 36 districts (59.1 %), while in 21 (34.4 %) – morbidity rates exceeded the territorial average. Cumulative dynamics of anthrax morbidity as regards livestock in Altai Territory in 1953–2015 showed downward trends. Complex evaluation of the situation and forecast of epidemic process development, employing composite index – epizootiological index and zoning of the territory according to the risk of epidemic complications – allows for the improvement of managerial decisions with the view to adequate anti-epidemic measures.